2020
DOI: 10.1111/jcpe.13324
|View full text |Cite
|
Sign up to set email alerts
|

Oral health‐related quality of life impacts are low 27 years after periodontal therapy

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 35 publications
1
17
1
Order By: Relevance
“…Therefore, these parameters were not considered further. However, it should be noted that a recent study found a statistically significant difference between OHIP-G14 summary scores of SPT-patients with Eichner class A1-B2 versus C2 (Graetz et al, 2020) and that the number of antagonistic contacts is a possible confounder of the present study. Although PT achieved an improvement of the periodontal situation in both groups, persisting PPD ≥6 mm and/or furcation involvement ≥degree II were still present in a high number of patients.…”
Section: Discussioncontrasting
confidence: 62%
“…Therefore, these parameters were not considered further. However, it should be noted that a recent study found a statistically significant difference between OHIP-G14 summary scores of SPT-patients with Eichner class A1-B2 versus C2 (Graetz et al, 2020) and that the number of antagonistic contacts is a possible confounder of the present study. Although PT achieved an improvement of the periodontal situation in both groups, persisting PPD ≥6 mm and/or furcation involvement ≥degree II were still present in a high number of patients.…”
Section: Discussioncontrasting
confidence: 62%
“…The treatment needs of the patients should not be hampered during this pandemic, but instead should be further prioritized, as there are restrictions of movement, limited access to dental care, and fear of cross-infections from dental clinics. Resolving this issue would offer more benefits than containing the progression of periodontal disease in the population, as it would also improve the quality of life of patients ( 57 , 58 ) with long-term supportive care ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…ucsf.edu/trial/NCT04409873, https://clinicaltrials.gov/ct2/show/ NCT04341688) that could help provide safe alternatives to dental practices and healthcare for the public at large. Continuous periodontal care for periodontitis patients is of the utmost importance and must be done in a timely manner to prevent progression and reinfection of the disease, especially among high-risk individuals (53)(54)(55)(56). Progression and reinfection of periodontal pockets does not only have implications for oral health, but also systemic health, given the bidirectional link between periodontal disease and common non-communicable diseases such as diabetes mellitus, rheumatoid arthritis, and hypertension, and those who are immune suppressed.…”
Section: Discussionmentioning
confidence: 99%
“…Responses can be summed up in each domain and overall. The total OHIP-14Sp sum score can range from 0 to 56, and higher scores indicate a poorer OHRQoL (Graetz et al, 2020).…”
Section: Data Collectionmentioning
confidence: 99%